Effect of 0.05% Sodium Fluoride Mouthwash on Surface Roughness and Friction Between Ceramic Brackets and Rhodium-Coated and Uncoated Stainless Steel Wires - Tahereh Hosseinzadeh Nik; Hannaneh Ghadirian; Tabassom Hooshmand; Mohammad Javad Kharrazi fard; Maryam Nasiri; Maryam Javaheri Mahd (Tehran University of Medical Sciences, 2019)
Objectives: This study aimed to assess the effect of 0.05% sodium fluoride (NaF) mouthwash on the surface roughness and friction between ceramic brackets and rhodium-coated (RC) and uncoated stainless steel (SS) wires. Materials and Methods: This experimental study was performed on 48 maxillary premolar ceramic brackets. Twenty-four pieces of RC-SS wires were used. Samples were divided into four groups. Groups 1 and 2 were immersed in artificial saliva, and groups 3 and 4 were immersed in a solution consisting of artificial saliva (9%) and mouthwash (91%). To assess surface roughness, images were obtained from the surface of wires and brackets with atomic force microscopy (AFM) and scanning electron microscopy (SEM) before and after the intervention. To assess friction, the wires were ligated into brackets, and friction was measured at a crosshead speed of 0.5 mm/minute using a universal testing machine. Data were analyzed using one-way analysis of variance (ANOVA) at the 0.05 significance level. Results: Friction during sliding in RC wires was significantly less than that in SS wires (P<0.05). Increase in the friction in SS wires by mouthwash was significantly greater compared to RC wires (P<0.05). Surface roughness coefficients of the wires before the intervention were not significantly different. The surface roughness of the wires significantly increased after the intervention and it was greater in SS wires than in RC wires (P<0.05). Conclusions: Considering the lower friction and surface roughness of SS-RC wires compared to SS wires, SS-RC wires may be a better alternative for use with ceramic brackets.